Herbal medicine and leptospirosis in Southeast Asia: A comprehensive bibliometric analysis (1973-2023) - Shah Putri Ade Dian; Stefani Widodo; Putri Damayanti Irma; Halim Shariff; Abidah Safithri; Muhammad Almanfaluthi (BIO Web of Conferences)
This study provides a bibliometric analysis of research on herbal medicine and leptospirosis in Southeast Asia from 1973 to 2023. The investigation identified 3,043 documents through a systematic search in the Scopus database using keywords. One hundred forty-seven papers were published across 100 different sources, revealing an annual growth rate of 6.07%, indicating a growing interest in the intersection of herbal medicine and leptospirosis. The study shows significant collaboration, with 935 authors contributing to the body of research and an average of 7.55 co-authors per document. Notably, 40.14% of the publications involve international co-authorship, reflecting the global relevance and collaborative efforts in addressing leptospirosis through herbal remedies. Keyword analysis highlights “leptospirosis,” “leptospira,” and “DNA extraction” as central themes, demonstrating a focus on the genetic and diagnostic aspects of the disease alongside the exploration of plant-based treatments. The research also emphasizes the role of preclinical studies and the chemical analysis of herbal remedies for leptospirosis. The study identifies key contributors to the field, with prolific authors such as Chee HY, Sekawi Z, and Patarakul K leading the research efforts. Malaysia, Thailand, and Japan are highlighted as the most productive countries, significantly contributing to this domain’s research output and citation impact.